Integration Of Defense Policy And Public Policy In Countering Hybrid Warfare Threats: A National Security Analysis Approach - Sianturi, Kristomei; Supriyadi, Asep Adang (UNIVERSITAS PAKUAN, 2025)
The management of border areas plays a strategic role in maintaining Indonesia's sovereignty and national stability. As an archipelagic state with extensive land and maritime borders, Indonesia faces complex challenges such as transnational threats, smuggling activities, human trafficking, maritime piracy, and potential territorial conflicts. This article analyzes national security strategies in border management through the integration of public policy and state defense. The study adopts a descriptive qualitative approach using literature review methods, emphasizing the synergy between military defense, defense diplomacy, advanced technology (such as artificial intelligence, drones, and satellites), and economic-social policies. The findings reveal that the application of AI-based surveillance systems and big data analytics enhances early detection capabilities against border threats. Moreover, the development of border economic zones and community empowerment programs such as MSMEs, education, and healthcare contribute to strengthening socio-economic stability and preventing local communities from engaging in illegal activities. The study also highlights the importance of international cooperation, both through bilateral agreements and regional forums such as ASEAN, in strengthening cross-border surveillance systems. With a comprehensive and collaborative approach, border management serves not only as an instrument of defense but also as an integral part of national development. This research is expected to offer strategic recommendations for improving Indonesia’s border policy amidst the ongoing shifts in global geopolitical dynamics